Hubungan Status Gizi dan Kepatuhan Diet Rendah Garam pada Pasien Hipertensi Rawat Inap di Rumah Sakit PKU Muhammadiyah Surakarta - Arini, Desinta, Setyaningrum Rahmawaty, A., M.Kes., Ph.D, Wahyuni, SSt. FT. M.Kes (2016)
Background: Hypertension can be caused by several risk factors, including gender, heredity, obesity, lack of exercise, smoking, and stress. Low salt diet and therapy is one of the treatment of hypertension. Diet adherence of hypertensive patients to low-salt diet is necessary to help the patient stay healthy. Objective: To determine the relationship between nutritional status and low-salt diet adherence in hypertensive patients at the PKU Muhammadiyah Hospital, Surakarta. Methods: The study is using cross sectional method, with consecutive sampling technique. Thirty hospitalized hypertensive patients in Multazam Room were recruited to participate in this study. Statistical test using the Spearman rank test. Results: 9 (30%) patients with normal nutritional status, and 9 (30%) patients with moderate hypertension obesity. While 8 (26.66%) patients did not follow the diet, 5 (16.7%) patients with higher nutritional status, 5 (16.7%) patients with malnutrition, and 2 (6.7%) patients with obesity. Twenty two (73.33%) patients follow the low salt diet. There was no significant relationship between nutritional status and low-salt diet adherence in (p = 0.557). Conclusions: Nutritional status of hypertensive patients in Multazam room PKU Muhammadiyah Hospital is not related to their low salt diet adherence